Issues in governance, growth and globalization in Asia (World Scientific, 2014)
"This volume is a compilation of important papers relating to the financial, governance and political-economy structures of the region, through a variety of methods and topics. Following the Asian crisis and subsequent global financial upheavals, policymakers and academics issued cries for institutional reform at the state and firm level; in many cases, reform was actually implemented rather than simply rhetorical. This volume begins by addressing issues relating to corporate governance within firms located in East Asia and as entities participating in corporate ownership elsewhere. Next, the key issues of globalization are directly addressed, including foreign direct investment into the region, integration among Southeast Asian countries and with the rest of Asia, and multinational enterprise investment strategy in Asia following initial entry decisions. Finally, the macroeconomic policies of state actors, and the effects of economic growth are examined"-- Provided by publisher.